The vulnerability of rural elderly Indonesian people to disability: an analysis of the national socioeconomic survey - Mardiana Puspitasari; Mugia Rahardja; Maria Gayatri; Adhi Kurniawan (Rural and Remote Health, 2021)
Introduction: There is a high prevalence of elderly people aged 65 years and older with disabilities in low- and middle-income countries, including Indonesia. This study examined urban-rural disparities in disabilities among elderly Indonesian people by adopting the International Classification of Functioning, Disability and Health scheme. Methods: The cross-sectional design used a sample of 16 054 people aged 65 years and over from the 2018 National Socio-Culture and Education Module of the National Socio-Economic Survey (Susenas-MSBP). Disability was measured by functional status questionnaires of Susenas that had adopted the UN Washington Group's short set of disability questions. The threshold was at least one of the six domains coded 'a lot of difficulty' or 'can't do it all', or two of the six domains coded 'some difficulty'. Logistic regression analysis was performed to examine disability-associated factors. Results: The prevalence of disability in this study was 35.1%. Among adults aged ≥65 years, those aged ≥85 years had the highest odds of having a disability (odds ratio (OR) 4.57, 95% confidence interval (CI) 4.54-4.59). Unemployed elderly people had a higher risk of disability than employed elderly people (OR 2.48, 95%CI 2.47-2.49). Elderly people who did not participate in leisure activities were 1.8 times more likely to have a disability than those who participated in leisure activities. Elderly people were more vulnerable to disabilities if they were female, unmarried, had a low balanced protein intake, and had health conditions. Physical exercise was a protecting factor against disability among elderly people. Compared with the results for elderly urban people, percentages for high educational attainment, high balanced protein intake, and leisure activities were lower for elderly rural people. Conclusion: Elderly rural people in Indonesia were more vulnerable to disabilities than elderly urban people were, which could be attributed to lower educational attainment, a lower balanced protein intake, and fewer leisure activities. As a result, the importance of socializing with family or friends, a high balanced protein intake, and leisure activities in assisting elderly rural people with disability issues must be emphasized.